Surface Damage Introduced by Diamond Wire Sawing of Si Wafers: Measuring in-depth and the Lateral Distributions for Different Cutting Parameters. Issue 1770 (2015) - Sopori, Bhushan; Devayajanam, Srinivas; Basnyat, Prakash; Schnepf, Rekha; Sahoo, Santosh; Gee, James; Severico, Ferdinando; Seigneur, Hubert; Schoenfeld, Winston V.; Preece, Steve; Binns, Jeff; Appel, Jesse; et al.
ABSTRACT: This paper describes the characteristics of damage, introduced under different conditions of diamond wire sawing, on the Si wafer surfaces. The damage occurs in the form of frozen-in dislocations, phase changes, and microcracks. The in-depth damage was determined by conventional ways such as TEM, SEM and angle-polishing/defect-etching, which only provide local information. We have also applied a new technique based on sequential measurement of the minority carrier lifetime after etching thin layers from the surfaces to determine average damage depth and its in-depth distribution. The lateral spatial damage variations, which seem to be mainly related to wire reciprocation process, were observed by photoluminescence and lifetime mapping. Our results show a strong correlation of damage depth on the diamond grit size and wire usage.